2016
DOI: 10.1016/j.jascer.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Red emitting phosphors based on titanite with high thermal stability

Abstract: Red emitting phosphors based on titanite, (Ca 1−x−y Eu x Na y)TiSiO 5+ı (x = 0.05, 0.07, 0.10; y = 0, 0.01, 0.03, 0.05), were synthesized by the conventional solid state reaction method, and their photoluminescence properties were investigated. Among (Ca 1−x Eu x)TiSiO 5+ı (x = 0.05, 0.07, 0.10), (Ca 0.93 Eu 0.07)TiSiO 5+ı (x = 0.07) showed the highest emission intensity of 14% in comparison with the commercial (Y 0.98 Eu 0.02) 2 O 2 S phosphor. Introduction of monovalent Na + into the (Ca 0.93 Eu 0.07)TiSiO 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…This frequency is consistent with the charge-band band detected in the absorbance range. The blue radiance was attributed to emanation from tetravalent titanium (4 +) particles because of the 4s-3d progress of titanium (3 +) particles, identified with charge-move excitations from 2p states of xxygen (2À ) to 3d ones of titanium (4 +), or shifts related with fluorine(+) focuses [140]. Also, through precise examination under various conditions, the discharge may be due to polyethylene glycol chains.…”
Section: Methods Applied On the Metal Surface 41 Surface Coating With...mentioning
confidence: 99%
“…This frequency is consistent with the charge-band band detected in the absorbance range. The blue radiance was attributed to emanation from tetravalent titanium (4 +) particles because of the 4s-3d progress of titanium (3 +) particles, identified with charge-move excitations from 2p states of xxygen (2À ) to 3d ones of titanium (4 +), or shifts related with fluorine(+) focuses [140]. Also, through precise examination under various conditions, the discharge may be due to polyethylene glycol chains.…”
Section: Methods Applied On the Metal Surface 41 Surface Coating With...mentioning
confidence: 99%
“…The MCW-LEDs model with flat silicone layer was created using LightTools 8.1.0 program and Monte Carlo method. The modeling process has been carried out in two steps: (1) the type of MCW-LEDs optical configuration and identification of components optical characteristics (2) SrBaSiO 4 :Eu 2+ concentration was constantly changed under careful monitoring to understand its influence on the optical performance of the MCW-LED. The optical performance of YAG:Ce 3+ and SrBaSiO 4 :Eu 2+ in MCW-LED lamps was calculated and compared to other configurations to verify the attained results.…”
Section: Construction Of Mcw-ledsmentioning
confidence: 99%
“…In recent years, most studies in solid-lighting industry have been focusing on enhancing optical properties of LEDs configuration, a new lighting method with outstanding performance. The expected results have been achieved, in particular, the crucial quality aspects of white LED lamps, luminous flux, and color homogeneity were discussed and improved in the previous studies [1][2][3][4][5]. For instance, Anh et al while studying the compound of SiO 2 particles and YAG:Ce 3+ phosphor observed the potential of phosphor compound and applied it to enhance white light [6].…”
Section: Introductionmentioning
confidence: 99%